1977
DOI: 10.7164/antibiotics.30.50
|View full text |Cite
|
Sign up to set email alerts
|

Microbial reduction of the side-chain carbonyl of daunorubicin and N-acetyldaunorubicin.

Abstract: Microorganisms reduced the side-chain carbonyl of daunorubicin to yield 13-dihydrodaunorubicin (daunorubicinol; daunomycinol). This microbial transformation occurred under aerobic conditions in agitated baffled shake flasks incubated at 37°C . The microorganisms were first grown in a medium which supported dense growth. Daunorubicin-HCl was then added. Following a period of incubation, broths were adjusted to pH 10.0 and extracted with chloroform. Daunorubicinol was recovered and purified from the chloroform e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…[4][5][6][7][8] The antitumor activity of a novel antibiotic, saframycin A, with a unique structure consisting of a dimer of 6-methyl-7-methoxy-1,2,3,4-tetrahydroisoquinoline-5,8-dione, as the basic skeleton, has been reported . [9][10][11][12] In our studies on the microbial conversion of SA into antibiotics possessing antitumor spectra different from those of the parent compound (SA), reduction of the side chain carbonyl group of SA was observed.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] The antitumor activity of a novel antibiotic, saframycin A, with a unique structure consisting of a dimer of 6-methyl-7-methoxy-1,2,3,4-tetrahydroisoquinoline-5,8-dione, as the basic skeleton, has been reported . [9][10][11][12] In our studies on the microbial conversion of SA into antibiotics possessing antitumor spectra different from those of the parent compound (SA), reduction of the side chain carbonyl group of SA was observed.…”
mentioning
confidence: 99%
“…3) The general appearance of the PMR spectrum of compound 4 both as free base and as hydrochloride was similar to that of 13-dihydrodaunorubicin (3, daunorubicinol)4~7) the only difference being the absence of the methoxy signal and the presence of an additional phenolic OH signal. Mild acid hydrolysis afforded a red aglycone (7) and an aminotrideoxysugar, C6H13O3N, which was identified as daunosamine (3-amino-2,3,6-trideoxy-L-lyxo-hexose)8) by direct comparison with an authentic sample. The aglycone (7) showed IR ( Tables 2 and 3.…”
Section: Structure Determinationmentioning
confidence: 99%
“…It has been shown that steffimycin (1) and steffimycin B (2) are reduced at the C-10 carbonyl by Actinoplanes utahensis, UCR-5885 and Chaetotnium sp., UCR-4634, respectively. Using cell-free extracts of the latter organism, the optimum conversion time, pH, and enzyme concentration have been determined for the conversion of 2 to 4.…”
mentioning
confidence: 99%